Herpes virus entry mediator signaling blockade produces mortality in neonatal sepsis through induced cardiac dysfunction - Wakeley, Michelle E.; Denning, Naomi-Liza; Jiang, Jihong; De Paepe, Monique E.; Chung, Chun-Shiang; Wang, Ping; Ayala, Alfred (Frontiers in Immunology, 2024)
Introduction Sepsis remains a major source of morbidity and mortality in neonates, and characterization of immune regulation in the neonatal septic response remains limited. HVEM is a checkpoint regulator which can both stimulate or inhibit immune responses and demonstrates altered expression after sepsis. We hypothesized that signaling via HVEM would be essential for the neonatal response to sepsis, and that therefore blockade of this pathway would improve survival to septic challenge. Methods To explore this, neonatal mice were treated with cecal slurry (CS), CS with Anti-HVEM antibody (CS-Ab) or CS with isotype (CS-IT) and followed for 7-day survival. Mice from all treatment groups had thymus, lung, kidney and peritoneal fluid harvested, weighed, and stained for histologic evaluation, and changes in cardiac function were assessed with echocardiography. Results Mortality was significantly higher for CS-Ab mice (72.2%) than for CS-IT mice (22.2%). CS resulted in dysregulated alveolar remodeling, but CS-Ab lungs demonstrated significantly less dysfunctional alveolar remodeling than CS alone (MCL 121.0 CS vs. 87.6 CS-Ab), as well as increased renal tubular vacuolization. No morphologic differences in alveolar septation or thymic karyorrhexis were found between CS-Ab and CS-IT. CS-Ab pups exhibited a marked decrease in heart rate (390.3 Sh vs. 342.1 CS-Ab), stroke volume (13.08 CS-IT vs. 8.83 CS-Ab) and ultimately cardiac output (4.90 Sh vs. 3.02 CS-Ab) as well as a significant increase in ejection fraction (73.74 Sh vs. 83.75 CS-Ab) and cardiac strain (40.74 Sh vs. 51.16 CS-Ab) as compared to CS-IT or Sham animals. Discussion While receptor ligation of aspects of HVEM signaling, via antibody blockade, appears to mitigate aspects of lung injury and thymic involution, stimulatory signaling via HVEM still seems to be necessary for vascular and hemodynamic resilience and overall neonatal mouse survival in response to this experimental polymicrobial septic insult. This dissonance in the activity of anti-HVEM neutralizing antibody in neonatal animals speaks to the differences in how septic cardiac dysfunction should be considered and approached in the neonatal population.